Making money for COVID-19. Issue 3 (25th July 2020) - Ward, Michael
Abstract : Learning outcomes: The case describes the origins of money, touching on the gold standard, the Fed's 1942 purchase of US debt to fund the "war effort", Bretton Woods (1944), Nixon's 1971 pulling the currency peg and descent of money from gold to fiat. It also touches on theories of inflation and deflation, quantitative easing (QE) post the 2008 crisis and the "swamp" of (unorthodox) modern monetary theory (MMT). Aside from providing a brief history of monetary policy and economics, the case study seeks to widen students' understanding of key economic issues including: fiat money, QE, government funding mechanisms, taxation, economic stimulation, inflation/deflation – and of course, the need for an ombudsman to limit excess. Case overview/synopsis: In May 2020, South Africa's deputy finance minister David Masondo announced that he would support the South African Reserve Bank's lending to the government. This statement followed President Ramaposa's earlier announcement of a R500bn COVID-19 stimulus package. The case explores the economic history of money, from barter to gold to cryptos. The case examines the origins of central banks' printing of money, initially to support the Second World War effort and more recently the 2008 global financial crisis and now the COVID-19 crisis. In particular, the case raises the question of central bank independence – "democratically elected governments always need money, is it appropriate for central banks provide it? And are there limits?" Complexity academic level: MBA and Executive Education Supplementary materials: Teaching Notes are available for educators only. Subject code: CSS: 1 Accounting and Finance.